A Novel Plate Compartment–Confrontation Method Discovered That Volatile Organic Compounds Produced by Saccharomyces cerevisiae Inhibit Botrytis cinerea and Fusarium graminearum - Ying Meng; Jing Wang; Hui Xu; Yaqi Yu; Yongheng Liang (Journal of Fungi)
Biological control of plant diseases is important for crop production. Botrytis cinerea and Fusarium graminearum are two common pathogenic fungi which result in great harm to crop production, processing, and storage of foodstuffs. Yeasts have unique advantages to be the focus of biological control of plant diseases through multiple mechanisms, including producing volatile organic compounds (VOCs) with inhibitory effect. However, the discontinuous display of inhibitory effect by yeast VOCs on pathogenic fungi is restricted by the conventional confrontation method, and the inhibitory mechanisms are unclear. We developed a new method to detect the inhibitory effect of Saccharomyces cerevisiae (yeast) VOCs on B. cinerea and F. graminearum. Our results showed that the yeast VOCs inhibited the growth and development of B. cinerea and F. graminearum and the strength of the inhibitory effect is positively related to the yeast inoculation amount. We confirmed the inhibition effect of ethyl acetic, one of the main yeast VOCs, on both pathogenic fungi. We further found that the deletion or overexpression of the ethyl acetic synthesis-related genes (ATF1 and/or ATF2) did not change the inhibitory effect much. The overexpression of ATF1 changed the main composition of VOCs. One of the changed VOCs, phenethyl acetic, even had stronger inhibitory effect than ethyl acetic on F. graminearum when they were added alone. These results suggest that the inhibitory effect of yeast VOCs on pathogenic fungi is a complex module. The lonely added individual component of VOCs may inhibit the growth and development of pathogenic fungi, while the partial alternation of VOC composition through gene modification may not be enough to change the total inhibitory effect.